Design of a binary weighted multilevel voltage source inverter for renewable energy purposes - Obais, Abdulkareem Mokif; Mukheef, Ali Abdulkareem (International Journal of Applied Power Engineering (IJAPE), 2025)
The flexibility and linearity of renewable energy generation techniques motivate the efforts to find high-performance circuitries capable of integrating the generation stations of renewable energy with the utility grid. As a result of its potential for power modules exploited in new generations of semiconductor switching devices, the voltage source inverter (VSI) has become widespread in the applications of renewable energy systems. In this paper, a new configuration of multilevel VSI is introduced. It is constructed of a unidirectional voltage supply having 15-nonzero levels and feeding a single-phase VSI equipped with an extra-freewheeling circuit. The output voltage of this configuration has 31 different voltage levels following a sinusoidal path. The unidirectional voltage supply is built of eight solid-state switching devices and four binary weighted DC voltage sources, which are realized by using appropriate solar panels. The simulation results of the introduced configuration have revealed almost sinusoidal output voltage and current for both inductive and resistive appliances. The number of employed switching devices is largely reduced compared to a conventional multilevel VSI. No harmonic reduction circuit or traditional pulse width modulation technique is employed in the current design. This system is designed and tested on PSpice.